Experimental Verification for Numerical Flow Analysis in Mixing Vessel - Kano, Masaya; Furukawa, Haruki; Kato, Yoshihito; Tanemori, Yuta; Shudo, Yuya; Mitome, Takahito; Yamada, Tsuyoshi; Yamashita, Kazuhiro (Journal of Chemical Engineering Research Updates, 2022)
Visualization of a streak line pattern in a mixing vessel is quite useful for understanding the mixing mechanism and designing an optimal mixing vessel. However, conventional experimental methods for visualizing streak lines require a lot of time to construct impellers and prepare solutions. Although various commercial fluid analysis software has been developed, there are still no examples of its use for calculating streak lines in mixing vessels. A simulation method was developed to quickly evaluate the streak line pattern in a laminar mixing vessel by numerical analysis with commercial code. A commercial CFD code can calculate streak line patterns in a laminar mixing vessel. It was found that a lattice method was more suitable than a particle method for the simulation of the streak line.